O razlagi pravil gospodarskega pogodbenega prava ob sodbi VSL V Cpg 734/2020 in sklepu VS RS III DoR 65/2021 - Kranjc, Vesna (Podjetje in delo, 2021)
The article is a critique of the court's decision in a commercial dispute. Before discussing the specific contractual conditions of the contractual penalty and the court decision, the author draws attention to the special requirements of the legal rules of commercial contract law, as well as to the starting point for the interpretation of the disputed contractual content.
Keywords: application and interpretation of legal rules; commercial contract law; contract interpretation; contractual penalty; gospodarsko pogodbeno pravo; judgement VSL V Cpg 734/2020; pogodbena kazen; razlaga pogodb; sodba VSL V Cpg 734/2020; uporaba in razlaga zakonskih pravil